Should We Perform Thoracic Imaging for Every Patient with a Renal Mass? - BOZKURTLAR, EMİNE; BATIREL, HASAN FEVZİ; TİNAY, İLKER; ŞENER, TARIK EMRE (GALENOS YAYINCILIK, 2016)
Objective: Current guidelines for the management of renal mass recommend thoracic imaging for potential metastatic nodules. Small size of the renal mass can be associated with low metastatic potential, which might question the necessity of thoracic imaging in this patient population. This study sought to evaluate the association of thoracic imaging findings with the renal mass characteristics in patients with pathologically proven renal cell carcinoma (RCC). Materials and Methods: We performed a retrospective analysis of patients with RCC, who underwent radical/partial nephrectomy and had baseline thoracic imaging available for review. Patients with a suspicious pulmonary mass were evaluated by the Department of Thoracic Surgery. Presence of lung nodule(s) and metastasis was determined and compared with patient and renal mass characteristics. Results: A total of 215 patients were included in the study. Pulmonary nodules suspicious for malignancy were present in 26.8% of the cases and 42% of these patients underwent further examination for the presence of a pulmonary mass. Pathological examination of the pulmonary nodule revealed RCC metastasis in 80% of patients who underwent biopsy or excision of the pulmonary nodule. Of note, in the subgroup analysis according to the pathological stage of the renal mass, 19.3% of patients with pT1a disease had a suspicious pulmonary mass on thoracic imaging. Of these patients, 25% underwent further examination of the pulmonary nodule with a RCC metastasis in 66.6%. Conclusion: The presence of suspicious lung nodules in patients with RCC has metastatic potential regardless of the size of the renal mass. These findings underscore the importance of baseline thoracic imaging and vigilant further evaluation of patients in whom pulmonary nodules are identified.
Keywords: Renal cell carcinoma; pulmonary metastasis; renal mass; thoracic imaging; FEATURES; TUMORS